PENGARUH MOTIVASI KERJA DAN KETERLIBATAN KERJA TERHADAP KEPUASAN KERJA PERAWAT PADA RSIA ERIA BUNDA PEKANBARU - Afriani Dewi; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of work motivation and work involvement on job satisfaction partially and simultaneously. This study uses a questionnaire as a tool for collecting data distributed to 71 respondents to the nurse at mother and child hospital Eria Bunda Pekanbaru. The data is then processed using descriptive analysis and statistical analysis using SPSS 16 by conducting validity test, reliability test, simple linear regression analysis, multiple linear analysis, analysis of determination (R2) and hypothesis testing by testing t test (partial) and F test (simultaneous).The results that the first hypothesis testing was work motivation for job satisfaction, t count (32,350) > t table (2,760), meaning that work motivation has a significant effect on job satisfaction. Second, work involvement is t count (7,150) > t table (2,760), meaning that work involvement has a significant effect on job satisfaction. The result of the F test count (757,712) > F table (3,139), meaning that work motivation and work involvement simultaneously have a significant effect on job satisfaction. Keywords: Work Motivation, Work Involvement, Job Satisfaction.